پاکستان میں تخفیف غربت کے ادارہ جاتی اقدامات: اسلامی تعلیمات کی روشنی میں تحقیقی جائزہ: Institutional Initiatives for Poverty Alleviation in Pakistan A Research Review in the Light of Islamic Teachings - Usama Ali, Hafiz Muhammad; Haider, Dr. Ghulam (Journal of Quranic and Social Studies, 2023)
Poverty is a reality that no one can deny. Because there are poor people all over the world. Economically weak people are left behind in every sphere of life. Islam also encourages improving economic life. In the Holy Qur'an, Allah Ta'ala has ordered cooperation with the poor people and has also announced a great reward for this action. The Holy Prophet (peace and blessings of Allah be upon him) not only issued orders to help the poor, but he was always seen following these orders. Islam has given special emphasis on poverty alleviation. It has given a solid and comprehensive program by following which it is possible to reduce poverty in the society. In this article, a review of the institutional measures taken for poverty alleviation in Pakistan is presented. Along with this, efforts have been made to bring forward the Islamic teachings which are meant for poverty alleviation. Because this problem can be eliminated only by following the principles of sanhar given by Islam. Not only is poverty a hindrance to social development, but it also has a profound effect on the morals and beliefs of the affected person. Because Allah Almighty has made the right to earn an income equal for all human beings and the true relationship of livelihood is with Allah Almighty and he is also the helper of every person. Therefore, the eradication of poverty is possible only if the economic system given by Allah is implemented.